1994
DOI: 10.1126/science.8108729
|View full text |Cite
|
Sign up to set email alerts
|

Age of the Earliest Known Hominids in Java, Indonesia

Abstract: 40Ar/39Ar laser-incremental heating of hornblende separated from pumice recovered at two hominid sites in Java, Indonesia, has yielded well-defined plateaus with weighted mean ages of 1.81 +/- 0.04 and 1.66 +/- 0.04 million years ago (Ma). The hominid fossils, a juvenile calvaria of Pithecanthropus and a partial face and cranial fragments of Meganthropus, commonly considered part of the Asian Homo erectus hypodigm, are at least 0.6 million years older than fossils referred to as Homo erectus (OH-9) from Olduva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
184
0
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(196 citation statements)
references
References 23 publications
5
184
0
7
Order By: Relevance
“…The genus Homo evolved in Africa at some time ca. 2 Ma [all older contenders to Homo status are debatable (3,4)], then rapidly spread out of its natal continent to populate Eurasia for the first time (5,6). The first truly cosmopolitan species of Homo, Homo heidelbergensis, is first known from Africa at ca.…”
mentioning
confidence: 99%
“…The genus Homo evolved in Africa at some time ca. 2 Ma [all older contenders to Homo status are debatable (3,4)], then rapidly spread out of its natal continent to populate Eurasia for the first time (5,6). The first truly cosmopolitan species of Homo, Homo heidelbergensis, is first known from Africa at ca.…”
mentioning
confidence: 99%
“…Movius, 1948; Beltwood, 1985; Keates, 1994) and that other mammals, including carnivores, megaherbivores, bovids, and equids dispersed between Africa and Asia without aid of Acheulean technology (Kurten, 1968; Antures, 1989; Opdyke, 1995). Likewise, hints from radiometric dating suggested that ex-African hominid sites existed in Southeast Asia much in excess of 1.0 Ma (Jacob & Curtis, 1971).Recent work in Java has confirmed not only the greatest age of 1.81 Ma for Mojokerto (Perning I), but has also shown that the main hominid bearing strata at Sangiran are all older than 1.0 Ma (Swisher et al, 1994;Swisher, 1996). Other Asian and West Asian sites have also been suggested to predate 1.0 Ma including Longuppo (China, 1.8 Ma), Dmanisi (Georgia, 1.7 Ma), and Ubeidiya (Israel, 1.3-1.4 Ma; Tchernov 1987;Huang et al, 1995).…”
mentioning
confidence: 82%
“…Recent work in Java has confirmed not only the greatest age of 1.81 Ma for Mojokerto (Perning I), but has also shown that the main hominid bearing strata at Sangiran are all older than 1.0 Ma (Swisher et al, 1994;Swisher, 1996). Other Asian and West Asian sites have also been suggested to predate 1.0 Ma including Longuppo (China, 1.8 Ma), Dmanisi (Georgia, 1.7 Ma), and Ubeidiya (Israel, 1.3-1.4 Ma; Tchernov 1987;Huang et al, 1995).…”
Section: Introductionmentioning
confidence: 92%
“…The long chronology suggests that the oldest hominin fossils are >1.5 Ma in the Sangiran dome and 1.8 Ma at Modjokerto according to 40 Ar/ 39 Ar analysis of hornblende samples (Swisher et al, 1994;Larick et al, 2001). At Sangiran, a high-resolution paleomagnetic record that documents the MatuyamaBrunhes transition (Hyodo et al, 2011), fission-track dating (Suzuki and Wikarno, 1982;Suzuki et al, 1985), faunal analysis (van den Bergh et al, 2001), and dating of tektites contradict this long chronology.…”
Section: Geochronologymentioning
confidence: 99%